Atypical Afta Major Healing after Photodynamic Therapy - Cinzia Casu; Carla Mannu (Hindawi Limited, 2017)
The aim of this study is to report a case of atypical Afta Major healing in a patient with recurrent aphthous stomatitis (SAR) with a type of photodynamic therapy. A female patient with SAR affected for about 2 years reported a history of hypothyroidism treated with Levothyroxine. The oral cavity clinical examination showed several major symptomatic ulcers, previously treated with topical and systemic therapies without any benefit. The largest of them is present for more than 40 days, in spite of topical cortisone applications, with significant pain symptoms reported by the patient. It was decided to perform a session of photodynamic therapy with a device that emits a LED light used in combination with a photosensitive reagent (Toluidine blue). The dye was applied on the entire surface of the lesion beyond the margins and even encroaching on healthy tissue. The light diode was turned on with a wavelength of 630 nm with cycles from 30 seconds, 10 consecutive times above it. After a few days, a curious phenomenon happened: healing of Afta Major starting from the center, which was almost completely healed towards the borders of the lesion. No previous literature reports this type of healing. Photodynamic therapy could be a successful treatment for SAR.